2009
DOI: 10.1007/s10571-009-9361-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neuron Specific Enolase and Malondialdehyde in Patients After Out-Of-Hospital Cardiac Arrest

Abstract: Estimation serum concentrations of NSE but not MDA seems to be a predictor of fate of patients after CA. The exact nature of oxidative stress can only be resolved by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…The present survey shows that most of the studies investigating biochemical markers and SSEP for the prediction of neurological [9] GOS 1-2 vs. GOS [3][4][5] No IMA and MDA At discharge Zandbergen et al [10] GOS No NSE 12 months Bassetti et al [11] GOS 1-2 vs. GOS [3][4][5] No NSE 12 months Hachimi-Idrissi et al [12] Modified GOS Yes S100B At discharge Pfeifer et al [13] GOS 1-2 vs. GOS [3][4][5] No NSE and S100B 28 days Rech et al [14] GOS 1-2 vs. GOS 3-5 No NSE 6 months Yanagawa et al [15] CPC 1-2 vs. CPC [3][4][5] Biochemical-hematologic parameters 1 month Derwall et al [16] CPC 1-2 vs. CPC 3-5 No S100B 14 days Steffen et al [17] CPC 1-2 vs. CPC [3][4][5] No NSE At discharge Tiainen et al [18] CPC 1-2 vs. CPC 3-5 No NSE and S100B 6 months Prohl et al [19] CPC 1-2 vs. CPC 3-5 Yes NSE and S100B 6 months Reisinger et al [20] CPC 1-2 vs. CPC 3 vs. CPC 4 Yes NSE 6 months Zingler et al [21] CPC 1-3 vs. CPC 4-5 Yes NSE and S100B 12 weeks Arnalich et al [22] Survivors vs. non-survivors No Cell-free plasma DNA 24 h and overall in-hospital mortality Auer et al [23] Survivors vs. non-survivors No NSE 48 h after ROSC Sulaj et al [24] Survivors vs. non-survivors No NSE and MDA 7 days Böttiger et al [25] Brain damage vs. no brain damage Yes NSE and S100B 7 days Meynaar et al [26] Comatose vs. regained consciousness Yes NSE During hospital stay Martens et al [27] Death/vegetative state vs. regained consciousness Yes NSE and S100B 6 months outcome after CA failed to exclude patients without certified brain death from the group of patients with poor outcome. If deaths after CA are included in neurological outcome studie...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present survey shows that most of the studies investigating biochemical markers and SSEP for the prediction of neurological [9] GOS 1-2 vs. GOS [3][4][5] No IMA and MDA At discharge Zandbergen et al [10] GOS No NSE 12 months Bassetti et al [11] GOS 1-2 vs. GOS [3][4][5] No NSE 12 months Hachimi-Idrissi et al [12] Modified GOS Yes S100B At discharge Pfeifer et al [13] GOS 1-2 vs. GOS [3][4][5] No NSE and S100B 28 days Rech et al [14] GOS 1-2 vs. GOS 3-5 No NSE 6 months Yanagawa et al [15] CPC 1-2 vs. CPC [3][4][5] Biochemical-hematologic parameters 1 month Derwall et al [16] CPC 1-2 vs. CPC 3-5 No S100B 14 days Steffen et al [17] CPC 1-2 vs. CPC [3][4][5] No NSE At discharge Tiainen et al [18] CPC 1-2 vs. CPC 3-5 No NSE and S100B 6 months Prohl et al [19] CPC 1-2 vs. CPC 3-5 Yes NSE and S100B 6 months Reisinger et al [20] CPC 1-2 vs. CPC 3 vs. CPC 4 Yes NSE 6 months Zingler et al [21] CPC 1-3 vs. CPC 4-5 Yes NSE and S100B 12 weeks Arnalich et al [22] Survivors vs. non-survivors No Cell-free plasma DNA 24 h and overall in-hospital mortality Auer et al [23] Survivors vs. non-survivors No NSE 48 h after ROSC Sulaj et al [24] Survivors vs. non-survivors No NSE and MDA 7 days Böttiger et al [25] Brain damage vs. no brain damage Yes NSE and S100B 7 days Meynaar et al [26] Comatose vs. regained consciousness Yes NSE During hospital stay Martens et al [27] Death/vegetative state vs. regained consciousness Yes NSE and S100B 6 months outcome after CA failed to exclude patients without certified brain death from the group of patients with poor outcome. If deaths after CA are included in neurological outcome studie...…”
Section: Discussionmentioning
confidence: 99%
“…7 studies used the GOS [8][9][10][11][12][13][14], which per se does not differentiate between death and brain death, while 4 studies using the GP-CPC did not restrict GP-CPC 5 to brain death [15][16][17][18]. Of all 20 studies, 13 studies did not further differentiate patients who died with respect to death by certified brain damage or death due to other reasons [8][9][10][11][13][14][15][16][17][18][22][23][24], while 7 studies did [12,[19][20][21][25][26][27].…”
Section: Studies Evaluating Biochemical Markers To Predict Outcome Afmentioning
confidence: 99%
“…17 Impairment of blood-brain barrier integrity and neuronal damage can be detected by the elevation of plasma neuron-specific enolase (NSE) and S-100B. 18,19 In this proof-of-concept, randomized, 3-arm (RIPC, sham, control group) clinical trial, we tested whether RIPC was safe and effective to reduce ischemic brain lesions on DWI after a CAS procedure, improve clinical outcomes at 6 months, and decrease plasma hs-CRP levels in subjects who underwent CAS. In addition, we examined plasma NSE and S-100B to determine the effects of RIPC on brain injury.…”
mentioning
confidence: 99%
“…In bipolar disorder, Andreazza et al [14] found elevated S100B and superoxide dismutase (SOD) activity-an enzyme scavenger of superoxide anion-both in manic and depressed patients. Also NSE levels were found to be increased in patients suffering cardiac arrest, together with high concentrations of malondialhehyde (MDA), a lipid oxidation product [15]. However, we found no reports relating antioxidant capacity modifications in essential HT with subclinical nervous tissue damage.…”
Section: Introductionmentioning
confidence: 72%
“…Although this does not exclude the possibility of our results being influenced by therapy, it indicates at least that multi-medication does not seem to enhance this effect, if present. The association of blood markers for CNS damage and oxidative stress has been explored in treatment refractory schizophrenics and in individuals who had suffered cardiac arrest, where increased NSE and lipid peroxidation (MDA and 4-hydroxinonenal, 4-HNE) concurred [15] [32]. Medina-Hernández et al [33] suggested that elevated MDA and 4-HNE might alter the permeability of the neuronal cytoplasmic membrane, consequently facilitating the release of NSE.…”
Section: Discussionmentioning
confidence: 99%